Pharmacological targets for the induction of ferroptosis: Focus on Neuroblastoma and Glioblastoma - Ferrada, Luciano; Barahona, María José; Salazar, Katterine; Godoy, Alejandro S.; Vera, Matias; Nualart, Francisco (Frontiers in Oncology, 2022)
Neuroblastomas are the main extracranial tumors that affect children, while glioblastomas are the most lethal brain tumors, with a median survival time of less than 12 months, and the prognosis of these tumors is poor due to multidrug resistance. Thus, the development of new therapies for the treatment of these types of tumors is urgently needed. In this context, a new type of cell death with strong antitumor potential, called ferroptosis, has recently been described. Ferroptosis is molecularly, morphologically and biochemically different from the other types of cell death described to date because it continues in the absence of classical effectors of apoptosis and does not require the necroptotic machinery. In contrast, ferroptosis has been defined as an iron-dependent form of cell death that is inhibited by glutathione peroxidase 4 (GPX4) activity. Interestingly, ferroptosis can be induced pharmacologically, with potential antitumor activity in vivo and eventual application prospects in translational medicine. Here, we summarize the main pathways of pharmacological ferroptosis induction in tumor cells known to date, along with the limitations of, perspectives on and possible applications of this in the treatment of these tumors.